2010
DOI: 10.1063/1.3418622
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous magnetic field effects during pulsed injection metal-organic chemical vapor deposition of magnetite films

Abstract: We report on large external magnetic field effects during pulsed injection metal-organic chemical vapor deposition of magnetite films on MgO͑001͒. The application of a 1 T field during the growth process significantly increases the saturation magnetization of magnetite by 150%-220% at a deposition temperature of 550 and 600°C, while the enhancement of the remanent magnetization is even larger. This anomalous magnetic field effect does not drastically alter the crystalline texture, surface morphology, and film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previously, we have demonstrated that the application of a 1 T magnetic field during magnetite film growth significantly alters the magnetic properties without any visible changes in crystalline texture, surface morphology, and film thickness [37]. This anomalous magnetic behaviour was explained by the reduction in antiphase-boundary formation during film growth as it was confirmed by TEM analysis.…”
Section: Introductionmentioning
confidence: 67%
“…Previously, we have demonstrated that the application of a 1 T magnetic field during magnetite film growth significantly alters the magnetic properties without any visible changes in crystalline texture, surface morphology, and film thickness [37]. This anomalous magnetic behaviour was explained by the reduction in antiphase-boundary formation during film growth as it was confirmed by TEM analysis.…”
Section: Introductionmentioning
confidence: 67%
“…In some studies [11,12], it has already been confirmed that the saturation magnetization can increase with the application of magnetic field. Especially in the case of Fe 3 O 4 thin films, 1 T field increases the saturation magnetization for 150%-200% [13]. But so far the reason why the saturation magnetization was increased is still unclear.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, it has been mentioned by some researchers that the presence of oxides, particularly magnetite (Fe 3 O 4 ), on the surface of magnetic materials could have a positive impact on their electromagnetic behaviour (Zukova et al , 2010). In this investigation, the exact composition of the oxides present on the surface of the steel could not be determined by X-ray diffraction, given that they were only found on the surface of the steel in the form of scattered islands and not as a continuous film.…”
Section: Discussionmentioning
confidence: 99%